2006
DOI: 10.1124/jpet.106.105999
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gabapentin and Ethosuximide for Treatment of Acute Nonconvulsive Seizures following Ischemic Brain Injury in Rats

Abstract: Acute seizures following brain injury have been associated with a worsening of patient outcome, but they are often undiagnosed and untreated when they occur without motor convulsions. Here, we sought to compare the antiseizure profile of ethosuximide (EXM; 125-312.5 mg/kg i.v.) and gabapentin (GBP; 0.3-50 mg/kg. i.v.) in a rat model of nonconvulsive seizures (NCS) induced by brain ischemia. Seizures were detected by continuous electroencephalographic monitoring for 24 h following permanent middle cerebral arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 36 publications
5
37
2
Order By: Relevance
“…It is of potential therapeutic value in other neuropsychiatric disorders (25,52). In the present study, we demonstrated that ETH promotes adult hippocampal neurogenesis both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…It is of potential therapeutic value in other neuropsychiatric disorders (25,52). In the present study, we demonstrated that ETH promotes adult hippocampal neurogenesis both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 53%
“…This dose was selected on the basis of therapeutically or pharmacologically relevant levels of ETH, as described earlier (25,30). Rats in the control group received normal saline as vehicle.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations